2004
DOI: 10.1629/1757
|View full text |Cite
|
Sign up to set email alerts
|

Marketing of electronic resources: projects and experiences

Abstract: This article focuses on different projects and ideas for marketing electronic resources at the State and University Library Bremen, Germany. It outlines the advantages and disadvantages of various methods that were tried. The most successful projects were the ones focusing directly on different needs of the departments and working groups at the University. 57

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Washington State University (Bancroft et al, 1998) University of Connecticut (Betz et al, 2009) University of Sunderland (Edwards and Webb, 1999) State and University Library, Bremen, Germany (Ellis, 2004) Texas A&M University (TAMU) Libraries (Hart et al, 2001) Wayne State University (Holley and Powell, 2004) University of New England, Armidale, New South Wales, Australia (UNE) (Leong, 2007) Tanzanian academic and research institutions (Manda, 2005) University of South Florida (Metz-Wiseman and Rodgers, 2007) Trinity University (Millet and Chamberlain, 2007) University of Arkansas (Parker-Gibson, 1994) Science & Engineering (S&E) Library at UCSC (Soehner and Wei, 2001) University of Illinois at Urbana-Champaign (Song, 2006) Marie R. Kennedy. 2011.…”
mentioning
confidence: 99%
“…Washington State University (Bancroft et al, 1998) University of Connecticut (Betz et al, 2009) University of Sunderland (Edwards and Webb, 1999) State and University Library, Bremen, Germany (Ellis, 2004) Texas A&M University (TAMU) Libraries (Hart et al, 2001) Wayne State University (Holley and Powell, 2004) University of New England, Armidale, New South Wales, Australia (UNE) (Leong, 2007) Tanzanian academic and research institutions (Manda, 2005) University of South Florida (Metz-Wiseman and Rodgers, 2007) Trinity University (Millet and Chamberlain, 2007) University of Arkansas (Parker-Gibson, 1994) Science & Engineering (S&E) Library at UCSC (Soehner and Wei, 2001) University of Illinois at Urbana-Champaign (Song, 2006) Marie R. Kennedy. 2011.…”
mentioning
confidence: 99%
“…This study employed an analytical research survey. First, based on the literature, 56 methods of electronic resources marketing were identified [ 4 , 7 , 15 , 17 , 22 , 25 , 32 – 34 ]. In reviewing these methods, duplicate items were removed or integrated into other methods, resulting in the inclusion of 44 methods in a checklist.…”
Section: Methodsmentioning
confidence: 99%
“…The literature indicates that academic libraries use various methods for introducing databases to their users [ 4 , 8 , 17 , 20 , 22 , 25 ], and some previous studies divided methods of marketing electronic resources into several general categories [ 26 ]. Some technological methods of marketing electronic resources, like web advertisement, are widely used by libraries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This campaign consisted of placing printed handouts at reference desks and sending email advertisements to all undergraduate students. Ellis (2004) described some of the attempts to market electronic resources at an academic library by providing training courses. The study revealed that fewer people attended general training courses than custom presentations about subject-specific databases.…”
Section: Literature Reviewmentioning
confidence: 99%